Distribution and population structure of Scopolia carniolica (Solanaceae) in the Dnieper Upland (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
Іnformation about distribution of rare species Scopolia carniolica in Ukrainіan flora on the Dnieper Upland (the Kiev, Zhitomir, Cherkassy and Kirovograd regions) is generalized. 20 locations of the species have been found within the region for the entire period of floristic studies. Among them, four locations have already been disappeared. One new locality has been described. Six local populations of S. carniolica are small or medium-sized and some of them have threatening status.
Keywords: сhorology, Red data book of Ukraine, plain part of Ukraine.